Do family environment, parental care and adolescent externalizing problem mediate the relationship between parental readiness and adolescent school performance among commuter families? - Siaw, Yan Li; Roslan, Samsilah; Abdullah, Maria Chong; Abdullah, Haslinda (Taylor & Francis, 2020)
The lifestyle of commuter families has become a concern in Malaysian society. Commuting and separation from nuclear families may result in negative impacts on the commuters and their families. This study aimed to investigate the relationships among family environment, parental care, parental readiness, and adolescent externalizing problems and adolescent school performance among commuter families by proposing a mediation model. A total of 434 respondents (dyadic-relation) from commuter families in Peninsular Malaysia completed a set of questionnaires. Model comparison showed that the mediation model was established with an acceptable fit index. Findings reported that parental care and family environment were significantly partial mediated the relationship between parental readiness and adolescent academic performance. However, adolescent externalizing problem was not statistically significant. The findings accounted 38% of the variability in adolescent academic performance explained by the model with total effect 0.69. Results suggests the importance of families’ roles and functions in adolescent school performance. It supports the theoretical backgroud of the research which explains the effect of family functions and parental roles in adolescent development and school performance. Parental roles need to be addressed to ensure commuting families play a parenting responsibilities in adolescent development and create a work-family balance situation. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.